Ecological Risk and Bioaccumulation of Heavy Metals and Pahs in Soil and Sida Acuta Around Power Stations in Lasustech, Nigeria - Sunmon, Odunayo Omodolapo; Yusuf, Afeez Olabisi; Odetunde, Simeon Kolawole; Odutayo, Funmilayo Kofoworola; Ademola, Adesina Micheal (Journal of Sustainability and Environmental Management, 2025)
This study assesses the contamination levels of heavy metals and polycyclic aromatic hydrocarbons (PAHs) in soil and Sida acuta around power stations within Lagos State University of Science and Technology (LASUSTECH), Nigeria. Soil samples revealed aluminum (Al) as the most abundant metal (79.24–128.17 mg/kg), with high manganese (Mn) concentrations at Location B (125.33 mg/kg). Lead (Pb) and nickel (Ni) were undetectable in some locations. Heavy metal analysis in Sida acuta indicated significant variability, with Al (5.22–14.35 mg/kg) and cadmium (Cd) detected only at Location A (1.16 mg/kg). PAH analysis using GC–MS identified phenanthrene and anthracene as dominant compounds, with peak concentrations at Locations A (245.76 µg/kg) and D (212.16 µg/kg), respectively. Sida acuta exhibited limited PAH uptake relative to soil, although slight accumulation of low-molecular-weight PAHs (e.g., naphthalene and phenanthrene) was observed, consistent with their higher solubility and mobility. Ecological risk assessments indicated Al as the most significant contaminant, with high contamination factor values, while the pollution load index (PLI) exceeded 1 in several locations, signaling pollution concerns. Bioaccumulation and translocation factors revealed substantial uptake of Al and Cd in Sida acuta, while PAH bioaccumulation remained generally low. These findings highlight potential ecological risks linked to power station emissions and underscore the need for regular environmental monitoring and soil–plant interaction assessments.